Analisis Peran Etika Profesi Dalam Meningkatkan Budaya Kerja Sebagai Penguatan Manajemen SDM: Studi Literatur Review - Adinda Desi Saputri; Evi Beatric Dewi Zebua; Halimah Tusakdiyah Nst; Agita Trianto; Bagas Indrianto Prasetio; ⁠Firhan Sudrajat; Dito Aditia Darma (PT PUBLIKASI INSPIRASI INDONESIA, 2026)
This study examines the increasing organizational need to strengthen a culture of integrity by internalizing professional ethics within human resource management (HRM). Persistent issues such as ethical violations, unfair practices, and a lack of professionalism indicate that moral values have not yet been fully embedded in shaping productive and sustainable work behavior. The purpose of this study is to analyze the role of professional ethics in improving work culture as a reinforcement of HRM through an extensive review of empirical and theoretical literature from national and international sources. The research adopts a library-based qualitative method, focusing on scholarly articles, books, and credible documents related to professional ethics, work culture, and contemporary HRM practices. The findings reveal four major roles of professional ethics: first, serving as a foundation for cultivating an integrity-based work culture by embedding values such as honesty, responsibility, and trustworthiness; second, guiding employees’ professional behavior through moral standards that support ethical decision-making; third, strengthening HRM systems by ensuring fair, transparent, and accountable policies; and fourth, enhancing productive work culture by fostering intrinsic motivation, discipline, and moral awareness in performing organizational tasks.